2017
DOI: 10.1016/j.appet.2017.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Associations between sociocultural home environmental factors and vegetable consumption among Norwegian 3–5-year olds: BRA-study

Abstract: The home environment is the first environment to shape childhood dietary habits and food preferences, hence greater understanding of home environmental factors associated with vegetable consumption among young children is needed. The objective has been to examine questionnaire items developed to measure the sociocultural home environment of children focusing on vegetables and to assess the psychometric properties of the resulting factors. Further, to explore associations between the environmental factors and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 42 publications
2
11
0
1
Order By: Relevance
“…Previous studies showed that parental eating behaviors, lifestyle, and dietary attitudes are associated with children's dietary habits. 23,24 Our results are consistent with these earlier results, indicating that parents have a significant impact on their children's dietary attitude and behaviors. Extending these results, we investigated more comprehensively the ways this may manifest.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed that parental eating behaviors, lifestyle, and dietary attitudes are associated with children's dietary habits. 23,24 Our results are consistent with these earlier results, indicating that parents have a significant impact on their children's dietary attitude and behaviors. Extending these results, we investigated more comprehensively the ways this may manifest.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, serving vegetables, berries and fruit in the home environment was also found to associate with children's fruit and vegetable consumption. The positive association between serving and children's fruit and vegetable intake is supported by previous studies conducted among under-school-aged children (Kristiansen, Bjelland, Himberg-Sundet, Lien, & Andersen, 2017a;Wyse, Campbell, Nathan, & Wolfenden, 2011). Surprisingly, serving vegetables, berries and fruit as part of an evening snack was not linearly associated with children's raw vegetables and fruit consumption.…”
Section: Discussionsupporting
confidence: 71%
“…The home environment is the first environment to shape children's relationship with food (Rosenkranz & Dzewaltowski, 2008). The fruit and vegetable consumption of under-schoolaged children has been shown to be associated with the home food environment, which includes the serving, availability and accessibility of food, family and child involvement, and parents' fruit and vegetable intake (Kristiansen, Bjelland, Himberg-Sundet, Lien, & Andersen, 2017a;Kristiansen, Bjelland, Himberg-Sundet, Lien, & Frost Andersen, 2017b;Wyse, Campbell, Nathan, & Wolfenden, 2011). The association between parents' fruit and vegetable intake and children's consumption of the food items has been mostly studied from a maternal point of view (Ong, Ullah, Magarey, Miller, & Leslie, 2017;Longbottom, Wrieden, & Pine, 2002) or by combining mother's and father's consumption habits to parental intake (Cooke et al, 2004;Fisher, Mitchell, Smiciklas-Wright, & Birch, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The parental feeding strategies for young children are known to result in differential effects on the healthiness of their children's diets [50,51]. Here, being permissive about their child's snacking promoted only unhealthy snack intake, whereas children's healthy snack intake was higher in parents who were specifically less permissive of, or less responsive to, unhealthy snacking.…”
Section: Discussionmentioning
confidence: 99%